Efficacy, safety, and cost-effectiveness of pegylated PEG-rhg-CSF in pediatric patients receiving high-intensity chemotherapy: results from a phase II study - Huang, Junting; Zhu, Jia; Jiang, Lian; Xu, Jiaqian; Lin, Xiheng; Chang, Jian; Zhang, Xiaohong; Lu, Suying; Sun, Feifei; Wang, Juan; Que, Yi; Ye, Zhonglv; et al. (Frontiers in Pharmacology, 2024)
Background: High-intensity chemotherapy can cause life-threatening complications in pediatric patients. Therefore, this study investigated safety and efficacy of long-acting pegylated recombinant human granulocyte colony-stimulating factor (PEG-rhG-CSF; Jinyouli ® ) in children undergoing high-intensity chemotherapy.Methods: Treatment-naive patients received post-chemotherapy PEG-rhG-CSF as primary prophylaxis for two cycles. The primary endpoints were drug-related adverse events (AEs) and bone pain scores. Secondary endpoints included grade 3-4 neutropenia, duration of neutropenia recovery, absolute neutrophil count changes, febrile neutropenia (FN), reduced chemotherapy intensity, antibiotic usage, and AE severity. The cost-effectiveness of PEG-rhG-CSF was compared with that of rhG-CSF (Ruibai ® ).Results: Here, 307 and 288 patients underwent one and two PEG-rhG-CSF cycles, respectively. Ninety-one patients experienced drug-related AEs, primarily bone pain (12.7%). Moreover, Grade 3-4 neutropenia and FN were observed. Median FN durations were 3.0 days in both cycles. No drugrelated delays were observed during chemotherapy. One patient experienced grade 4 neutropeniainduced reduction in chemotherapy intensity during cycle 2. In total, 138 patients received antibiotics. PEG-rhG-CSF exhibited superior cost-effectiveness compared to rhG-CSF.Our findings indicate that PEG-rhG-CSF is safe, efficient, and cost-effective in pediatric patients undergoing high-intensity chemotherapy, providing preliminary evidence warranting further randomized controlled trials.* Duration of neutropenia recovery data were not available for one patient in cycle 1 and for 32 patients in cycle 2. ANC, absolute neutrophil count; FN, febrile neutropenia.